HAMBATAN DOSEN PENDIDIKAN JASMANI DAN OLAHRAGA DI ERA PEMBELAJARAN DIGITAL - Syafruddin, Muhammad Akbar (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
This research is a quantitative descriptive study which aims to determine the obstacles experienced by physical education and sports lecturers in carrying out the lecture process in the digital era. The data analysis technique used is descriptive analysis. The sample used in this research was 35 physical education and sports lecturers in South Sulawesi Province. The data collection technique used is survey techniques using Google Form media. The research instrument used was a questionnaire with a Likert scale. The statement indicators consist of the learning media used, lecturers' attitudes towards the digitalization of education, lecturers' motivation in dealing with digital education, lecturers' creativity in carrying out learning, and supporting infrastructure for online learning. The conclusion of this research is that the biggest obstacles often experienced by lecturers in carrying out the lecture process are that the majority of lecturers still have difficulty operating computers, lack of lecturer knowledge regarding variations in learning media, difficulty for lecturers in determining appropriate learning methods during online lectures, and difficulty for lecturers to raise participant motivation. students during online lectures